How Does Violence Force Displacement during Active Conflict? : Evidence from the Republic of Yemen - D'Souza, Anna; Favari, Eliana; Krishnaswamy, Siddharth; Tandon, Sharad (World Bank, Washington, DC, 2022)
The ways in which violence forces displacement are not well understood given difficulties in collecting data during conflict. This paper investigates this issue during the Republic of Yemen's conflict, which has led to a large forced displacement crisis. First, it demonstrates that violence significantly escalated leading up to and following displacement in the districts from which displaced households fled, and this escalation exceeded that of households that did not become displaced and that of regions to which displaced households moved. Second, the paper demonstrates that the escalation of violence around the time of displacement varied by type of violence. Violence from ground battles escalated leading up to and following displacement- the type of violence with the largest number of fatalities per violent incident and that is most associated with the capture of territory; but other prevalent types of violence either peaked prior to displacement or did not appear to be strongly associated with displacement. And third, it demonstrates that there was a significant amount of heterogeneity in the violence experienced by households before displacement. A significant share of displaced households fled during times of no violence, but violence escalated in the regions from which these households fled following displacement. The paper argues that the last result is likely explained, in part, by these households being more averse to potential violence than other Yemeni households were. Combined, these results corroborate that violence is pivotal to forced displacement, but further illustrate the complexities of deciding whether and when to become displaced.